O PIBID na formação de educadores musicais: reflexões sobre os processos educativos na construção da identidade profissional - Ament, Mariana Barbosa (Universidade Federal de São Carlos, 2015)
This dissertation advocates for Humanizing Music Education, a term in education that places the human as priority, as well as its relations based on dialogue, curiosity, authonomy, otherness, amorousness, to be freedom through conscientization of educators and students about the potential and power to transform society. Authors that discuss education as Paulo Freire, Ernani Maria Fiori, Carlos Rodrigues Brandão, António Nóvoa, in consonance with authors from Music Education as Carlos Kater, Hans Joachim Koellreutter, Teresa Mateiro, Claudia Belochio, among others, help to comprehend this concept on analysing humanizing elements of education together with what we understand of music education of quality. For a truly humanizing music education, it is necessary to educate teachers in humanization, which could help in the process of humanization of their students. We believe that in initial education, teachers learn and teach in a way that could be very usefull for its professional development as educator. The research strived to study knowledge about the influence of a government scholarship program for teaching initiation on future music educators and the construction of its professional identity considering the program, one of the main incentives of teaching which offers partnerships between school and university in a process of mutual implementation for the teacher education. Seeking to know from music educators, what are their most significative learnings during their participation in the program and what those experiences helped them in the construction of their professional identity, three subjects that graduated in Music Education and participated in the program during their initial formation were choosen. Through documental analysis, we analysed portfolios selected and sent by the subjects to find education processes that occurs during their participation in the program. After gathering the portfolios, individual open-interviews were done so that the subjects could, with the researcher, remember some learnings, talk about their professional practices after the formation and how affirm their professional identity, they are: "Learning of Teaching", Possible methodologies and Professional Identity". From the data collection, three analisys categories arose and revealed learnings in teaching, possibilities for methodology strategies created by their own at school and comprehensions about professional identity of each one. In the analisys process, we realized that we must valorize and create more and more programs, projects and actions at university that approximate and or introduce the future educators at schools daily routine and more, valorize the learnings of own future educators as equally important part of the disciplinary avaliations that occurs at university. We hope, with this research contribute to the area of education and music education and show that, even that the music educator does not act at basic education as a professional, the learnings generated from school, as we could see, will also contribute to the acting in other fields of music education and education if made with compromisse, respect, in other words, more humanizing practices.
Keywords: Educação musical; Professores - formação; Práticas sociais e processos educativos; Programa Institucional de Bolsa de Iniciação à Docência; Humanizing music education; Teaching education; Educative processes; Institutional Program Initiation Grant to Teaching; Professional identity; CIENCIAS HUMANAS::EDUCACAO